METODE PERHITUNGAN INTENSITAS REKAHAN BATUAN GEOLOGI 3D MENGGUNAKAN SKELETONISASI - Prana F L Tobing; Selly Feranie; Fourier D. E. Latief (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Fracture plays important role in oil, gas, and geothermal reservoir because it is easier to flow the fluid than the porous medium that form of granules. Fracture intensity is one of the main parameters of fracture that indicate the number of fracture at any length or section. Previous studies of fracture intensity calculation are limited to 2D fracture, the determination of 3D fracture intensity is still not comonly found because its determination method still slightly. Therefore, in this paper we/ve applied skeletonization method to 3D rock fracture. Skeletonization is thickness transformation of sample image composer that represented by the color white in the image (pixel with â€œ1â€ value in the binary image) into a new image with the thickness of white is 1 pixel. Skeletonization usually used to characterize the length of binary image in digital image analysis. Rock fracture sampel in this paper were drawn for Kamojang Geothermal Area in cube form with side 3.5 cm. The sample has been applied in 3 different temperature condition i.e. room temperature (24Â° C), 300Â° C, and 600Â° C. The fracture intensity which has calculated in each temperature condition respectively are 2.995Ã—10-3 cm-2, 3.160Ã—10-3 cm-2, and 3.850Ã—10-3 cm-2. These result indicate that the increasing of temperature not only make the new fractures, it also causes the propagation of old fractures so that fracture intensity increases. These result are appropriate with the thoery of temperature effect on forming fracture. Thus, skeletonization method can be an alternative for calculation of 3D fracture intensity. Keywords: fracture, binary image, skeletonization.